Comparative Evaluation of Ethanolic Extracts of Bacopa monnieri, Evolvulus alsinoides, Tinospora cordifolia and their Combinations on Cognitive Functions in Rats - Gupta, Avneet; HemRaj; Singh Karchuli, Manvender; Upmanyu, Neeraj (Current Aging Science, 2013)
The effects of ethanolic extracts of whole plants of Bacopa monnieri (BME), Evolvulus alsinoides (EAE), Tinospora cordifolia (TCE) and their combinations in equal proportion [CEP-1 (BME+EAE), CEP-2 (BME+TCE), CEP-3 (EAE+TCE) and CEP-4 (BME+EAE+TCE)] were tested in amnesic rats using Radial arm maze task performance (RAM) and Barnes maze test at 200 mg/kg p.o. The latency to find food and target hole was observed in RAM and Barnes maze respectively. Cognitive dysfunction was induced by scopolamine (0.3 mg/kg i.p.) treatment. BME, EAE, TCE and their combinations of equal proportion (CEPs) showed significant decrease in latency to find food and target hole in RAM and Barnes maze respectively. Inter comparison among single extract alone treated groups revealed that BME treated animals showed significant difference as compared to EAE and TCE treated animals. All combinations of equal proportion (CEPs) of these extracts showed significant difference in latency to find food and target hole as compared to single extracts treated animals. CEP-1 showed significantly better effect as compared to CEP-2 and CEP-3. Significant difference in latency to find food and target hole was also present between CEP-2 and CEP-3. Effect of CEP-4 was found to be significantly better than CEP-1, CEP-2 and CEP-3 treated rats in both models. From present investigation, it was concluded that ethanolic extract of Bacopa monnieri, Evolvulus alsinoides and Tinospora cordifolia provided better nootropic effect when used in combination.
Keywords: nootropic